O comportamento decisório dos tribunais superiores como incentivo à modificação da conduta de agentes brasileiros pela poluição marinha por plástico - Lavôr, Amanda Rodrigues (2024)
The dissertation seeks to answer the following question: does the decision-making behavior of higher courts tend to modify the conduct of Brazilian agents due to marine plastic pollution? Over the years, humanity has gradually expanded its production and consumption capacity. As a result, the amount of waste generated in this process also increased and the treatment of this waste did not keep up with the exponential increase in its production, which led to the natural dumping of these materials in a disorderly and inadequate manner. Among such materials are plastics. In this context, the seas and oceans become one of the natural environments most affected by pollution caused by plastic. Given the gravity of the situation, seeking to guarantee the right to well-being, in a preventive and not just reparative manner, it is essential to unravel the role of the Judiciary. The scientific approach is plural and involves literature review, Content Analysis (CA), Decision Analysis Methodology (MAD), with a small-N research design and quali-quanti support. The research is classified as pure, given its purpose of expanding knowledge, and practical, as it investigates decision-making behavior of the courts and a solution to a given problem. The research is relevant from a theoretical and academic perspective as it promotes debate on the application of the principles of environmental law, sustainability as a systemic constitutional principle, as well as civil liability for environmental damage, in relation to marine pollution, in the decisions of Superior Courts . The practical relevance arises from the possibility of the response achieved giving greater visibility to environmental and sustainability issues, as well as providing technical-legal assistance to government actions for the formulation of public policies and national development programs in this regard. In response to the proposed questioning, it is identified that, after studying the collegial decisions, that the decision-making behavior of the higher courts directly leads to the conduct of Brazilian agents regarding marine plastic pollution, both in favor of a balanced environment and in favor of economic interests. From the analysis, it was found that the STF's decisions have a more environmentalist character, while those of the STJ have a mixed understanding.